Software technology for conducting simulation experiments with mathematical models of physiological systems - Aksnova, T.V. (Інститут програмних систем НАН України, 2018)
Based on the given analysis of existing systems the necessity of development of new flexible physiologist-researcher oriented system is shown. The developed system, which allows physiologists to build virtual organisms from the extendable set of blocks, is described.